The dynamics of Islamic marital jurisprudence in Islamic courts: the experience of the Kwara state and Zanzibar - Oba , Issa Babatunde (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2023)
Zanzibar is an island located in East Africa and part of the United Republic of Tanzania. In contrast, Kwara State is one of the states of the Federal Republic of Nigeria in the West Africa sub-region. Both regions have similar colonial histories and post-colonial experiences. Islamic Jurisprudence has undergone many reforms since the post-colonial era in Zanzibar Island of Tanzania and Kwara State of Nigeria. Islamic Jurisprudence is used in the adjudication process in Islamic religious courts in these two regions of Africa with a sizeable Muslim population. These courts essentially adjudicate Muslim personal matters, such as marriage, divorce, inheritance, wills, and endowment. The official jurisprudence of the people Zanzibar-Tanzania is Shafi’i jurisprudence. For the people of Kwara State of Nigeria, Maliki jurisprudence is recognized. Marriage is considered part of Muslim identity; therefore, applicable jurisprudence is necessary for a fair hearing on Muslim personal matters. The Muslim judges (qadis) play a laudable role in the justice system under Islamic Jurisprudence. This paper uses doctrinal, case law and empirical approaches for the discourse.